Pengaruh Pengetahuan Dan Sikap Kader Terhadap Perilaku Kader Dalam Penyuluhan Gizi Balita Di Posyandu Wilayah Kerja Puskesmas Ngemplak Kabupaten Boyolali - Ria Kusuma, Agnes; , Yuli Kusumawati, S.K.M., M. Kes (Epid); , dr. Rukma Astuti., M.PH (2015)
A positive knowledge and attitudes cadres will have an impact on the will of cadres to always proactive and responsible in giving the socialization of the importance of nutrition toddlers to the community. Research target to knowing the correlation about knowledge and an attitude toward behavior cadres in the implementation of the counseling nutrition babies in Posyandu the working areas of Ngemplak Health Center Ngemplak Sub District Boyolali District. Research Methods this research used observational analytic with cross sectional approach. Sample in research estimated 259 cadres .Research instruments uses a questionnaire .Analysis data using multiple linear regression at significant level 95 %. Result in partial knowledge and attitudes about nutrition toddlers significant to behavior cadres in counseling nutrition babies in posyandu the working areas of Ngemplak Community Health Center Ngemplak Sub District Boyolali District (p=0,000). Together knowledge and attitudes about nutrition toddlers significant to behavior cadres in counseling nutrition babies in posyandu the working areas of Ngemplak. Community Health Center Ngemplak Sub District Boyolali District 63% (p=0,000). Key Word: knowledge, attitudes, behavior cadres